Large-area few-layered graphene film determination by multispectral imaging microscopy1. Issue 19 (21st May 2015) - Wang, Hsiang-Chen; Huang, Shih-Wei; Yang, Jhe-Ming; Wu, Guan-Huang; Hsieh, Ya-Ping; Feng, Shih-Wei; Lee, Min Kai; Kuo, Chie-Tong
<x xml:space="preserve">Abstract</x> A multispectral imaging method is proposed for rapid and accurate identification of few-layered graphene using optical images.